Survival after Consecutive Myocardial Infarction and Stroke: A Case Report - Ratautė, Kristina; Burneikaitė, Greta; Badarienė, Jolita (Acta medica Lituanica, 2024)
Background: Myocardial infarction and stroke are prevalent and potentially fatal urgent medical conditions. Stroke as a subsequent cardiovascular event after the myocardial infarction significantly decreases the odds of survival for the patient.Clinical case: We report a case of a 48-year-old man admitted to Vilnius University Hospital Santaros Klinikos due to an ST-segment elevation myocardial infarction. Patient also experienced a cardioembolic cerebral infarction on the tenth day in the hospital. The patient survived this dual infarction, his general condition improved and he was discharged to the rehabilitation center.Discussion and Conclusions: Cardiovascular diseases are the most common cause of death in the world. Stroke, as a complication of myocardial infarction, affects 0.76–3.2% of patients and demonstrates an increasing incidence trend. In such a dual infarction, in-hospital mortality can be as high as 18–41%. It is hopeful that targeted research and evidence-based prevention with treatment can improve outcomes of concomitant myocardial infarction and stroke.
Keywords: myocardial infarction; stroke; cerebral infarction; mortality